2002
DOI: 10.1038/nature00793
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal weathering of apatite as an important calcium source in base-poor forest ecosystems

Abstract: The depletion of calcium in forest ecosystems of the northeastern USA is thought to be a consequence of acidic deposition and to be at present restricting the recovery of forest and aquatic systems now that acidic deposition itself is declining. This depletion of calcium has been inferred from studies showing that sources of calcium in forest ecosystems namely, atmospheric deposition and mineral weathering of silicate rocks such as plagioclase, a calcium-sodium silicate do not match calcium outputs observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
261
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 350 publications
(271 citation statements)
references
References 28 publications
9
261
0
1
Order By: Relevance
“…Calcium concentrations were declining before Euro-American settlement, and it is difficult to assess the role of anthropogenic activities in the 20th century from these sedimentary data alone. Nevertheless, this decrease in sedimentary Ca from 876 CE to the beginning of the presettlement period reflects a large depletion of the total Ca pool from upper soil horizons, and this pool remains a particular concern, as it is larger than the entire exchangeable Ca pool in the soil and the forest floor pool (10,25). …”
Section: Ca Depletion As a Natural Consequence Of Long-term Ecosystemmentioning
confidence: 99%
“…Calcium concentrations were declining before Euro-American settlement, and it is difficult to assess the role of anthropogenic activities in the 20th century from these sedimentary data alone. Nevertheless, this decrease in sedimentary Ca from 876 CE to the beginning of the presettlement period reflects a large depletion of the total Ca pool from upper soil horizons, and this pool remains a particular concern, as it is larger than the entire exchangeable Ca pool in the soil and the forest floor pool (10,25). …”
Section: Ca Depletion As a Natural Consequence Of Long-term Ecosystemmentioning
confidence: 99%
“…Hartmann et al, 2013). (Griffiths et al, 1994;Strobel, 2001;Blum et al, 2002). 토양 내 미생물에 의한 질산화 반응이 나 황화물의 산화과정, 또는 대기 중에서 침적되는 질 산이나 황산에 의해서도 토양의 풍화는 진행되고 토양 은 산성화될 수 있다 (Stark and Hart, 1997;Markewitz et al, 1998;Raymond and Oh, 2009 (Shukla and Mintz, 1982;Moulton et al, 2000).…”
Section: 이산화탄소가 화학적 풍화작용에 쓰이는 주요 반응 물이기 때문에 토양의 화학적 풍화작용은 육상 생태계unclassified
“…However, biotite persists in many soils, which indicates that biotite dissolution is incongruent in pH conditions common to soils and element release becomes diffusion-limited due to secondary phases/remnant silicate framework at the mineral surface [61]. Some agricultural studies showed that after tillage, the soils released more cations from clays [71], and in forests after disturbance, the cation nutrient release also increased for a short period of time [25,45,72], because these processes likely expose fresh mineral surfaces and enhance the temporary cation release from both primary and secondary minerals. However, with changing climate and water availability, the role of mycorrhizal associations in the nutrient acquisition of higher plants might increase in areas subjected to drier conditions in the future [73].…”
Section: Element Release Ratesmentioning
confidence: 99%